Microsoft SQL Server 2012 administration : real-world skills for MCSA certification and beyond : exams 70-461, 70-462, and 70-463 - Carpenter, Tom, 1972- (John Wiley & Sons, 2013)
Implement, maintain, and repair SQL Server 2012 databases As the most significant update since 2008, Microsoft SQL Server 2012 boasts updates and new features that are critical to understand. Whether you manage and administer SQL Server 2012 or are planning to get your MCSA: SQL Server 2012 certification, this book is the perfect supplement to your learning and preparation. From understanding SQL Server's roles to implementing business intelligence and reporting, this practical book explores tasks and scenarios that a working SQL Server DBA faces regularly and shows you step by ste.